2016
DOI: 10.1016/j.ejvs.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Muscle Area Predicts All-Cause Mortality After Endovascular and Open Aortic Aneurysm Repair

Abstract: PMA is independently associated with all-cause mortality after elective endovascular and open aortic aneurysm repair, and may be integrated into the pre-operative risk assessment to optimize care in high-risk frail patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 33 publications
2
70
0
Order By: Relevance
“…A CT scan prior to TAVI is routinely performed and PMA measures can be easily obtained. Furthermore, PMA can be measured with high reliability . In our study, we had nearly perfect intra‐observer and intra‐observer agreement.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A CT scan prior to TAVI is routinely performed and PMA measures can be easily obtained. Furthermore, PMA can be measured with high reliability . In our study, we had nearly perfect intra‐observer and intra‐observer agreement.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, PMA can be measured with high reliability. 15,16 In our study, we had nearly perfect intra-observer and intra-observer agreement.…”
Section: Discussionmentioning
confidence: 53%
“…There is a growing body of literature on the negative effect of sarcopenia on surgical outcomes and mortality. Both Lee et al and Drudi et al demonstrated increased risk of mortality after AAA repair with decreasing total psoas muscle (25,26). However, both studies defined sarcopenia based on the lowest tertile within the study group, making their definition susceptible to selection bias.…”
Section: Discussionmentioning
confidence: 96%
“…Limb Ischaemia Frailty Index. 25 Six single domain tools were used in 11 studies examining four areas: cognition, 7 function dependency, 32,33,38 central muscle mass, 10,11,36,37,39,40 and nutrition. 35 Six studies were conducted in patients who underwent major vascular surgery, 7,8,28,30,31,34 nine studies in patients with AAA, 11,12,14,27,33,36e39 and 10 studies in patients with LEAD.…”
Section: And Criticalmentioning
confidence: 99%